Quantifying lung aeration in neonatal lambs at birth using lung ultrasound - Pryor, Emily J.; Blank, Douglas A.; Hooper, Stuart B.; Crossley, Kelly J.; Badurdeen, Shiraz; Pollock, James A.; Stainsby, Andrew V.; Croton, Linda C. P.; O’Connell, Dylan W.; Hall, Christopher J.; Maksimenko, Anton; Hausermann, Daniel; et al. (Frontiers in Pediatrics, 2022)
Background: Lung ultrasound (LUS) is a safe and non-invasive tool that can potentially assess regional lung aeration in newborn infants and reduce the need for X-ray imaging. LUS produces images with characteristic artifacts caused by the presence of air in the lung, but it is unknown if LUS can accurately detect changes in lung air volumes after birth. This study compared LUS images with lung volume measurements from high-resolution computed tomography (CT) scans to determine if LUS can accurately provide relative measures of lung aeration. Methods: Deceased near-term newborn lambs (139 days gestation, term ~148 days) were intubated and the chest imaged using LUS (bilaterally) and phase contrast x-ray CT scans at increasing static airway pressures (0 cmH2O to 50 cmH2O). CT scans were analysed to calculate regional air volumes and correlated with measures from LUS images. These measures included (i) LUS grade; (ii) brightness (mean and coefficient of variation); and (iii) area under the Fourier power spectra within defined frequency ranges. Results: All LUS image analysis techniques correlated strongly with air volumes measured by CT (p<0.01). When imaging statistics were combined in a multivariate linear regression model, LUS predicted the proportion of air in the underlying lung with moderate accuracy (95% prediction interval ±22.15%, r2=0.71). Conclusion: LUS can provide relative measures of lung aeration after birth in neonatal lambs. Future studies are needed to determine if LUS can also provide a simple means to assess air volumes and individualise aeration strategies for critically ill newborns in real time.